Analiza laserskega rezanja hladno valjane pločevine za zahteven globoki vlek - Grum, Janez (Strojniški vestnik, 1999)
Studies conducted on the condition of a surface macrostructure and microstructure and the subsurface of a cut, confirm that by measuring various roughness parameters the laser cutting process can be optimized very successfully. Different energy inputs and various modes of laser beam operation allowed us to ascertain that the major influences on cut quality were exerted by beam power and cutting speed, which determine the amount of energy transferred to the cutting front. The results of our studies conducted so far, and the experience gained in assessment of the laser cut quality, confirm that knowledge of the lower and the upper cutting speeds is necessary to determination the optimum parameters for laser cutting. A result of poor circular polarization is that the cut quality depends on the cutting direction.
Keywords: rezanje lasersko; hrapavost površin; makroanalize; mikrotrdota; lasersko rezanje; rezanje; pločevina; površine; odrezavanje; trdota; mikrostruktura